Keeping the moon - Dessen, Sarah (New York Viking, 1999)
Fifteen-year-old Colie, a former fat girl, spends the summer working as a waitress in a beachside restaurant, staying with her overweight and eccentric Aunt Mira, and trying to explore her sense of self
1
Keywords: Aunts -- Fiction; Restaurants -- Fiction; Self-esteem -- Fiction; Weight control -- Fiction